Determination of Sustainable Behavior of Higher Education Students from a Gender Perspective Based on Household Electricity Consumption - Carlos GALLEGUILLOS; Rubén HURTADO; José SILVA; Lesly CORTES (Communications of International Proceedings, 2022)
The purpose of this research was to determine the sustainable behavior of higher education students, from a gender perspective based on electricity consumption in homes. An online survey was conducted with 309 university students. The results indicated that the students show favorability towards saving electricity. Regarding gender, there are significant differences between women and men in half of the questions. Finally, the discussion of the results, limitations and future lines of research are presented.
Keywords: sustainable behavior; energy use; climate change.